P84 The effect of establishing single site diagnostic services in improving lung cancer pathway timelines, to help implement the national optimal lung cancer pathway (NOLCP). (12th November 2019) - Millington, K; Marchand, C; Walters, J; Masani, V
Abstract : Lung cancer is the leading cause of cancer death in the UK. The National Optimal Lung Cancer Pathway (NOLCP) has been developed to improve timelines to diagnosis (28 days), time-to-treatment (49 days), and survival. The NOLCP presents appropriately challenging timelines, which may be difficult to achieve if diagnostic tests are performed in several different trusts. In order to adopt the NOLCP, our district general hospital introduced and re-organised services to facilitate all diagnostic tests being performed on a single site. We studied the effects of establishing all services on one site to facilitate the NOLCP. In particular we studied improvements in timelines for newly established Endobronchial Ultrasound (EBUS), local PET-CT and local anaesthetic thoracoscopy (LAT) services. Methods: Patient data was obtained from the cancer registry for all patients undergoing EBUS, PET-CT or LAT investigations. Data was collected over a 24-month period for each investigation (12-month periods before and after service introduction). Baseline patient demographics, investigations, and diagnosis were collected. Results: 375 patients were investigated by the Lung Multidisciplinary Team (MDT) over the study period. 156 patients were investigated prior to the establishment of local diagnostic services and 219 after the introduction of these services. We assessed the effect of introducing new local services on the referral to treatment times for these patients (Figure 1). The results identified reductions in all pathways for patients receiving new locally performed diagnostic tests. The timeline improvements were as follows: EBUS performed 7 days earlier, PET-CT 3.9 days performed earlier, LAT 31.7 days performed earlier. Discussion: Introduction of local diagnostic services, located on a single site, improved referral to treatment times for patients newly diagnosed with lung cancer. We believe it is likely these improvements are related to an increase in diagnostic capacity and improved efficiencies in the diagnostic pathway. These improvements have facilitated application of the NOLCP.